Evaluation of organic carbon content and source rock maturity using petrophysical logs and geochemical data: Case study of Horn Valley Siltstone source rock, Amadeus Basin, Central Australia - Shiri, Mahdi; Ranjbar-Karami, Rasoul; Moussavi-Harami, Reza; Rezaee, Mohammad reza (Sulaimani Journal for Pure and Applied Sciences, 2013)
In this study, 30 samples from the Horn Valley Siltstone Formation from Amadeus Basin in Central Australia have been analyzed using geochemical method Rock-Eval (RE) pyrolysis. The analysis shows Total Organic Carbon between 0.21 to 2.74%wt . It also shows that kerogen type II, and a mixture of type II and III are the dominant kerogen. This type of kerogens are prone to oil and oil/gas production. The geochemical diagrams show that all samples are in the oil window, and they have good thermal maturation. The Horn Valley siltstone formation has been divided into 4 zones; Hv1, Hv2, Hv3 and Hv4. Although all zones are mature (i.e., have Tmax over 435 °C), Hv2 has a high organic carbon content and is located at the end of the oil window (Tmax between 450-470 °C). Also, to compare the results, petrophysical logs (Resistivity and Sonic) and ΔlogR method were used to determine the organic carbon content of source rock, and investigate zones with high pontentials to produce hydrocarbons. Zones have the potential to produce hydrocarbons was determined. And there was a close adaptation between the results of petrophysical method (ΔlogR) and Rock-Eval pyrolysis technique. The results show that Petrophysical method (ΔlogR) and the Rock-Eval pyrolysis technique have produced close results
Keywords: Organic matter; RockEval pyrolysis; ΔlogR; Horn Valley Siltstone; Australia